Anemic Status and Academic Achievement at Female High School Students in Kapuas - M Muchtar; Dodik Briawan; Emmy S Karsin (Media Gizi dan Keluarga, 2000)
Research objectives were to analyze the association between anemic status and academic achievement of female students at high school. Sixty female students at the second grade at SMUN I Kuala Kapuas in Kapuas District were chosen as samples, which 30 students classified as anemic group and the rest of non-anemic. The anemic status was categorized based on the haemoglobin (Hb) by Sahli-test. Among 90 samples at the first screening, it was found 60 students having Hb < 12 g/dl. The proportion of anemic students were 66.7% and their average Hb was 11.2 g/dl Hb. Comparing the anemic and non-anemic groups, there were no significantly difference (p=0.613) of parents education term, total of family members (p=0.943), total income per capita (p=0.408), and iron intake (p=0.167). However, vitamin C intake was significantly different between anemics and non anemics students (p=0.001). There were significantly different between anemic and non anemic student at the academical achievement, where the subject score of Mathematic, Natural Science, and Social science (p=0.031) were higher among the non anemic than those anemic. Meanwhile, the score of Indonesian language and Literature subjects were no significantly difference. The correlation analysis showed the Hb values was highly associated with the academical score of Natural Science, Mathematic, and Social Science subjects, but not correlated at the Indonesian Language and Literature subjects.Keywords: anemia, academic achievement